Preventing Illegal Levies in Senior High School Public Services: Assessing the Role of the Anti-Extortion Task Force in Jambi Province - Hartati Hartati; Erwin Erwin; Fitria Fitria; Beny Saputra (Universitas Lampung, 2026)
This study examines the effectiveness of the Saber pungli Task Force in preventing illegal levies in senior high school public services in Jambi Province using an empirical legal (socio-legal) approach with qualitative methods. Data were collected through in-depth interviews with task force members, school administrators, teachers, and other education stakeholders, supported by regulations, reports, and institutional records. The findings indicate that, although the task force has adequate institutional authority to implement prevention and enforcement measures, its effectiveness remains constrained by structural and cultural challenges, including weak internalization of anti-corruption values in schools, low public reporting, and limited participatory oversight. The study recommends strengthening complaint mechanisms, integrating anti-corruption policies into school governance, and improving legal literacy among education stakeholders. These findings contribute to the development of clean education governance and collaborative corruption prevention at the regional level.